2008
DOI: 10.1128/iai.00789-07
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the SitABCD, MntH, and FeoB Metal Transporters to the Virulence of Avian Pathogenic Escherichia coli O78 Strain χ7122

Abstract: The roles of SitABCD, MntH, and FeoB metal transporters in the virulence of avian pathogenic Escherichia coli (APEC) O78 strain 7122 were assessed using isogenic mutants in chicken infection models. In a single-strain infection model, compared to 7122, the ⌬sit strain demonstrated reduced colonization of the lungs, liver, and spleen. Complementation of the ⌬sit strain restored virulence. In a coinfection model, compared to the virulent APEC strain, the ⌬sit strain demonstrated mean 50-fold, 126-fold, and 25-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 67 publications
5
83
0
1
Order By: Relevance
“…The roles of these systems in virulence, independently or in combination, remain to be established. Recently, SitABCD has been shown to contribute to virulence of APEC x7122 in the chicken infection model and, together with MntH, to mediate resistance to oxidative stress (Sabri et al, 2008). Apart from plasmid-borne factors, genes encoding for ferric yersiniabactin uptake (fyuA) and iron-repressible protein (irp2) have been detected by PCR in more than 65% of strains isolated from cases of avian colibacillosis (Janssen et al, 2001).…”
Section: Progress Towards Unravelling Apec Virulence Factorsmentioning
confidence: 99%
“…The roles of these systems in virulence, independently or in combination, remain to be established. Recently, SitABCD has been shown to contribute to virulence of APEC x7122 in the chicken infection model and, together with MntH, to mediate resistance to oxidative stress (Sabri et al, 2008). Apart from plasmid-borne factors, genes encoding for ferric yersiniabactin uptake (fyuA) and iron-repressible protein (irp2) have been detected by PCR in more than 65% of strains isolated from cases of avian colibacillosis (Janssen et al, 2001).…”
Section: Progress Towards Unravelling Apec Virulence Factorsmentioning
confidence: 99%
“…In APEC strains, sit genes are highly associated with virulence in 1-day-old chicks, and there is a prevalence of this system in virulent isolates when compared with fecal commensals (40,123). Interestingly, although sit genes are also found on the chromosome of some E. coli strains, the sitABCD operon in APEC strains is mainly plasmid-encoded (124).…”
Section: Sitabcd Iron Transport Systemmentioning
confidence: 99%
“…After its initial identification as a siderophore-independent iron ABC transporter, the Sit system was shown to be involved in manganese and ferrous iron transport from the periplasm to the cytoplasm (116,121,122). The ability of the SitABCD transport system to transport manganese might enhance resistance to oxidative stress and survival in extraintestinal tissues (123).…”
Section: Sitabcd Iron Transport Systemmentioning
confidence: 99%
“…Furthermore, several studies have suggested that the expression of an iron acquisition system occurs mainly in APEC compared with AFEC (Dias da Silveira et al, 2002;Dozois et al, 1992;Emery et al, 1992;Linggood et al, 1987). Among APEC strains, iron acquisition systems can be encoded by genes located on plasmids (Sabri et al, 2008;Skyberg et al, 2006) or by chromosomal PAIs (Kariyawasam et al, 2006a). …”
Section: Iron Acquisition Mechanismsmentioning
confidence: 99%
“…The salmochelin biosynthesis and transport genes have generally been found on large pathogenic plasmids; ColV or ColBM, as well as, on the chromosome in APEC strains . The salmochelin system is involved in the virulence mechanism of APEC strains (Sabri et al, 2008;Sabri et al, 2006) and includes sitABCDE in combination with other iron uptake systems. It can contribute to iron acquisition and to bacterial survival (Sabri et al, 2006).…”
Section: Salmochelinmentioning
confidence: 99%